39.4k views
2 votes
5y(2x-1)=y(x+2)+20, x=3​

User Rafaella
by
5.4k points

2 Answers

2 votes

5y(2x-1)=y(x+2)+20, x=3​

Step 1: Substitute x with 3

5y(2(3) - 1) = y(3 + 2) + 20

Step 2: Combine like terms in the parentheses

5y(6 - 1) = y(3 + 2) + 20

5y(5) = y(3 + 2) + 20

5y(5) = y(5) + 20

Step 2: Distribute the number outside the parentheses to the numbers inside the parentheses

25y = 5y + 20

Step 3: Combine like terms by subtracting 5y to both sides

25y-5y = (5y-5y) + 20

20y = 20

Step 4: Divide 20 to both sides to isolate y


(20y)/(20) = (20)/(20)

y = 1

Check:

5(1) (2(3) - 1) = 1(3+2) + 20

5(6-1) = 1(5) + 20

5(5) = 5 + 20

25 = 25

Hope this helped!

User Edson Medina
by
4.9k points
2 votes

Answer:

y=1

Explanation:

5y(2x-1)=y(x+2)+20, x=3

5y(2(3)-1)=y(3+2)+20

5y(6-1)=y(5)+20

5y(5)=5y+20

25y=5y+20

25y-5y=20

20y=20

y=20/20

y=1

User Paco Zarate
by
5.3k points